Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1186/1475-2859-8-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of folding modulators to improve heterologous protein production in Escherichia coli

Abstract: Despite the fundamental importance of E. coli in the manufacture of a wide range of biotechnological and biomedical products, extensive process and/or target optimisation is routinely required in order to achieve functional yields in excess of low mg/l levels. Molecular chaperones and folding catalysts appear to present a panacea for problems of heterologous protein folding in the organism, due largely to their broad substrate range compared with, e.g., protein-specific mutagenesis approaches. Painstaking inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 183 publications
1
60
0
2
Order By: Relevance
“…When lacking specific knowledge of suitable chaperones, screens for expression in the presence of combinations of chaperones can be conducted [55]. A comprehensive review examining the advantages and disadvantages of this approach can be found in a review by Kolaj et al [56].…”
Section: Induction and Co-expression With Chaperonesmentioning
confidence: 99%
“…When lacking specific knowledge of suitable chaperones, screens for expression in the presence of combinations of chaperones can be conducted [55]. A comprehensive review examining the advantages and disadvantages of this approach can be found in a review by Kolaj et al [56].…”
Section: Induction and Co-expression With Chaperonesmentioning
confidence: 99%
“…Proteins are folded into their final conformation, and the PelB leader is removed in the periplasm (5). Problems in the periplasm may have been encountered, such as periplasmic inclusion bodies, errors in folding or disulfide bond formation, or degradation (24,46). Any of these problems could explain why SM1 was detected in the cell pellet and not in the supernatant and why the anti-Pbs21 scFv was not detected in P. agglomerans.…”
Section: Discussionmentioning
confidence: 99%
“…In the widely used bacterium Escherichia coli, many strategies have been explored to enhance recombinant protein solubility. Among them, the coproduction of folding modulators, believed to be limiting in cells actively producing recombinant proteins, has attracted special attention (14). However, the efficacy of such an approach has been highly controversial.…”
mentioning
confidence: 99%
“…In contrast to the widespread use of folding modulators in bacteria (14), very few attempts have been made to improve cytoplasmic protein production in insect cells with the aid of We appreciate financial support through grants BIO2007-61194 and EUI2008-03610 (MICINN) to A.V. and grant BB/C504735/1 (BBSRC) to P.R.…”
mentioning
confidence: 99%